Mathematical Logical Problems as a Means of Developing Creative Thinking - Nikoghosyan, Gagik (Scientific Proceedings of Vanadzor State University: “Natural and Exact Sciences, 2023)
Key words: prove, refute, parity, divisibility, invariant, spatial body, development, skill It is known that one of the educational goals of the school course in mathematics is the formation and development of creative and logical thinking of students. Unfortunately, we have to state that in the development and implementation of new forms of training organization, sufficient attention is not paid to improving the content of training and, accordingly, to increasing efficiency. In the learning process, due attention is not paid to the formation and development of students’ intuition, analytical thinking, conjecture, the ability to draw reasonable conclusions, which is a serious obstacle to the development of their exploratory and creative thinking, scientific intuition. In this work, the task is to identify the contributing role of the logical tasks of proof or refutation, regarding spatial bodies and their developments in the process of formation and development of exploratory skills, logical and creative thinking of students, which is the scientific pedagogical novelty of the work. In particular, such logical problems of proof or refutation are considered, the solution of which is based on the method of using an invariant. In the first part of the article, the essence of the method of applying the invariant through the law of elimination of the middle is stated, then the problems of proof or refutation based on the principle of gradual complication are discussed, in the solution of which the invariant is directly applied. The second part of the work is devoted to logical problems related to spatial bodies. We consider logical tasks based on the principle of gradual complication, associated with spatial bodies and their sweeps, with the aim of developing the spatial and creative thinking of students through the latter.